Perbandingan Metode Rasional Dengan Kreatif Untuk Mendesain Alat Bantu Pasang Lampu - Rudy Firman Prakosa; Alva Edy Tontowi (Forum Teknik, 2010)
Abstract This article discusses the result comparison of design process of lamp installation device using rational and creative methods and its usability analysis. The study was conducted through team recruitment, prototype development, prototype selection, and usability testing. The teams recruited involved creative team (K-team) consisting of experienced technical expert and non-exact  students,  and  rational  team  (R-Team)  consisting  of  exact  students  with  knowledge  in product design method. Result of prototype selection using weighted objectives method showedthat  rational prototype  produced  higher  total  weight  compared  to  that  of  creative  prototype. Usability  testing  were  also  conducted  in  terms  of  rational  and  creative  prototype  methods. Usability  testing  involved  learnability,  error,  efficiency  of  use,  and  satisfaction.  Result  of usability testing showed that rational prototype had higher efficiency of use, lower error, and higher  satisfaction  level.  Therefore,  rational  method  becomes  better  design  process  in  lamp installation device.  Keywords: product design, creative method, rational method, usability, device